Factors Associated With Delayed Menopause in Iran, Based On Fasa Cohort Study, A Branch Of Persian Cohort Study: - Sharafi, Mehdi; Farjam, Mojtaba; Amiri, Zahra; Bahramali, Ehsan (Galen Medical Journal, 2018)
Background: Investigation of middle-aged women’s mental and physical health measures should be focused on menopause that is a predictable physiological phenomenon in their lives, because the prevalence of the majority of chronic diseases increases after this period. This study aimed to determine the risk factors of delayed menopause (climacterium tardum). Material and Methods: The current cross-sectional research was conducted on 1930 menopausal women who had referred to the cohort study of Fasa University of Medical Sciences during 2014-2015. The data were extracted from the database, and then, the variables were checked for accuracy. Finally, the data were analyzed using logistic regression analysis. Results: This study was conducted on menopausal women with the mean age of 57.98±5.8 years. Among the women, 1555 (80.6%) were married, and the rest were single and widowed. Besides, the mean age at menarche was 13.7±1.64 years. Additionally, 1726 women (89.4%) had experienced natural menopause, while the rest had experienced delayed menopause. The results of the multivariate analysis indicated that delayed menopause was associated with marital status, education level, age at menarche, occupation, abortion, and use of contraceptive methods. However, no significant relationship was found between delayed menopause and smoking, duration of lactation, duration of using contraceptive pills, and the number of childbirths. Conclusions: Considering the increased life expectancy among women, delayed menopause, and its risk factors should be taken into account. Although genetic factors play key roles in menopause age, the role of socio-demographic factors, such as marital status and pregnancy, should not be ignored. [GMJ.2018;7:e922]